A case of Beckwith–Wiedemann syndrome caused by a cryptic 11p15 deletion encompassing the centromeric imprinted domain of the BWS locus. Issue 6 (20th October 2009) - Zollino, Marcella; Orteschi, Daniela; Marangi, Giuseppe; De Crescenzo, Agostina; Pecile, Vanna; Riccio, Andrea; Neri, Giovanni
Abstract : Background: Beckwith–Wiedemann syndrome (BWS) is a clinically variable and genetically heterogeneous disorder, providing evidence that imprinted genes play key roles in the control of fetal growth. Clinically, diagnostic criteria include macrosomia, macroglossia, abdominal wall defects, neonatal hypoglycaemia, visceromegalies and hemihyperplasia. Component clinical manifestations also include renal abnormalities, adrenocortical cytomegaly and a characteristic facial appearance, with midface hypoplasia and ear anomalies. Genetically, BWS is associated with disturbances within two different domains on 11p15 that are controlled by distinct imprinting control regions (ICR), ICR1 and ICR2. The majority of patients have abnormalities within ICR2. In particular, loss of maternal methylation accounts for 50–60% of cases, and is associated with reduction in the expression of the CDKN1C gene, a member of the cyclin dependent kinase inhibitor family acting as negative regulator of cell proliferation. Mutations in CDKN1C are detected in another 5–10% of subjects with sporadic BWS. Chromosome deletions affecting ICR2 are uncommon. Methods and findings: We report on a patient with BWS in which a de novo 11p15 deletion was detected by array comparative genomic hybridisation. Clinically, the patient presented with mild mental retardation and minor physical anomalies. The deletion, that was demonstrated to be maternal in origin by SNP array, encompassed ICR2 and several flanking genes, including CDKN1C . A normal methylation pattern of ICR1 was observed. Conclusions: This observation provides evidence that, among the genetic defects associated with BWS, a 11p15 microdeletion encompassing ICR2 identifies a peculiar clinical phenotype, with high recurrence risk in offspring of female carriers. It also supports the model of two independent domains within the BWS locus.